2022
DOI: 10.1007/s00345-022-04204-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of same-day discharge following single-port robotic-assisted laparoscopic prostatectomy

Abstract: Purpose The standard discharge pathway following robotic-assisted laparoscopic prostatectomy (RALP) involves overnight hospital admission. Models for same-day discharge (SDD) have been explored for multiport RALP, however, less is known regarding SDD for single-port RALP, especially in terms of patient experience. Methods Patient enrollment, based on preoperative determination of potential SDD eligibility, commenced March 2020 and ended March 2021. Day-of-surgery criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Our LOS findings for SP versus MP in high complexity masses support these results. While fewer incisions may be a factor in shorter LOS for high complexity SP cases, (1) we did not observe a similar difference in low complexity cases, and (2) our study timeline overlapped the COVID-19 pandemic, which has been associated with significantly higher rates of same-day discharge after robot-assisted urologic surgery [ 17 , 18 ]. Other recent studies have noted decreased operative time and EBL for retroperitoneal MP-RAPN compared to the transperitoneal approach [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 93%
“…Our LOS findings for SP versus MP in high complexity masses support these results. While fewer incisions may be a factor in shorter LOS for high complexity SP cases, (1) we did not observe a similar difference in low complexity cases, and (2) our study timeline overlapped the COVID-19 pandemic, which has been associated with significantly higher rates of same-day discharge after robot-assisted urologic surgery [ 17 , 18 ]. Other recent studies have noted decreased operative time and EBL for retroperitoneal MP-RAPN compared to the transperitoneal approach [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 93%
“…Of the 51 patients eligible for SDD after SP-RALP, 15 underwent SDD, and 36 opted for standard discharge process due to various reasons such as pain, fatigue, other medical reasons, and nonmedical reasons related to distance from hospital and being a second start surgery. [ 3 ] Encouragingly, the study demonstrated comparable outcomes in regard to complications, 90-day readmission and 90-day emergency room visits between the SDD and standard discharge process.…”
mentioning
confidence: 84%
“…Of note, 24 studies comparing RS-RARP to other approaches have been published up to April 15, 2023. Most reports aimed to demonstrate differences between RS-RARP and other approaches in terms of early and late urinary continence (Table 1) [5–8,9 ▪ ,10,11 ▪ ,12–16,17 ▪ ,18,19 ▪ ,20–22,23 ▪ ,24 ▪▪ ,25–28], but none focused on erectile function as primary endpoint. A minority of the studies reported data on sexual function, never finding significant differences among the RARP approaches.…”
Section: Literature Overviewmentioning
confidence: 99%